1985
DOI: 10.1037/0096-1523.11.1.1
|View full text |Cite
|
Sign up to set email alerts
|

How much is an icon worth?

Abstract: We report a new technique for assessing the amount of information extracted from the icon that follows a briefly presented picture. The problem of how to measure such information was formulated in terms of how much physical exposure of a picture an icon is worth. Consider two types of stimulus presentations, each with a base duration of d ms. The first is a d-ms picture followed by an icon, and the second is a d + a-ms picture not followed by an icon. How large does a have to be so that equivalent amounts of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 27 publications
8
63
0
Order By: Relevance
“…In particular, the experience of having just seen the prime can be said to be equivalent to, or worth, dp-msec of physical exposure duration relative to not having just seen the prime. The reasoning embodied in this assertion is reminiscent of that offered by Loftus, Johnson, and Shimamura (1985). In their experiments, visual stimuli, shown for varying durations, were followed either by an immediate mask (assumed to destroy any iconic image) or by a mask that was delayed by 300 msec (assumed to allow an iconic image).…”
Section: Default Prediction Of the Basic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the experience of having just seen the prime can be said to be equivalent to, or worth, dp-msec of physical exposure duration relative to not having just seen the prime. The reasoning embodied in this assertion is reminiscent of that offered by Loftus, Johnson, and Shimamura (1985). In their experiments, visual stimuli, shown for varying durations, were followed either by an immediate mask (assumed to destroy any iconic image) or by a mask that was delayed by 300 msec (assumed to allow an iconic image).…”
Section: Default Prediction Of the Basic Modelmentioning
confidence: 99%
“…Column 10 provides the prime's worth, defined to be (dp-ReL) (see discussion above). Finally, for comparison with data reported by Loftus et al (1985) and Loftus et al (1992), column 11, the rightmost column, provides our estimate of the worth of the icon that followed the prime (recall that the prime was unmasked). The icon's worth was computed as d p , the duration needed by an unprimed (masked) stimulus to reach prime-only performance level, minus 50 msec, the physical duration of the prime.…”
Section: Stimuli and Apparatusmentioning
confidence: 99%
“…They then observed that performance curves for the immediate-mask and delayed-mask conditions were horizontally parallel, with the immediate-mask curve shifted to the right by 100 ms. That is, performance for a d-ms stimulus followed by an icon was identical to performance to a (d ϩ 100)-ms stimulus not followed by an icon. Loftus et al (1985) concluded that irrespective of the duration of the physical stimulus that it follows, "an icon is worth 100 ms of additional physical exposure duration" (p. 1). Reinitz, Wright, and Loftus (1989) used similar logic to investigate priming effects.…”
Section: Experiments 2: Primingmentioning
confidence: 99%
“…These conditions allow testing of a strong and unambiguous interactive GtL theory prediction that uses methodology and associated logic introduced by Loftus, Johnson, and Shimamura (1985; see also Loftus, Duncan, & Gehrig, 1992) for investigating the contribution to memory of an iconic image. Loftus et al (1985) presented stimuli at varying durations that were followed either by an immediate mask (which did not allow an icon) or by a 300-ms delayed mask (which did allow an icon).…”
Section: Experiments 2: Primingmentioning
confidence: 99%
See 1 more Smart Citation